ZODIAC LIGHT DETECTION BASED ON SKY QUALITY METER (SQM) DATA: PRELIMINARY STUDY - Hendro Setyanto; Hendra Agus Prastyo; Muhammad Basthoni; Fika Afhamul Fuscha; Saleh M. Al Saab (Fakultas Syari'ah dan Hukum UIN Walisongo, 2021)
Zodiacal light is a night sky phenomenon that can occur before or after dusk. Additionally, zodiacal light is referred to as false dawn (fajar kadzib) or false dusk. Zodiacal light is emitted by the dust leftovers of asteroids, comets, and other extraterrestrial objects colliding along the planet Mercury's orbit to Mars. This remaining material orbits the Sun in the same direction as the four planets. When the Sun illuminates the leftover dust, it appears as a zodiacal light in the hemisphere that experiences dawn or dusk. By using linear fittings we detect the presence of zodiacal light on the light curve of the night skybrightness. The Observations were made using a digital camera and SQM. From a number of observational data obtained at six locations, it shows that there is an identical linear pattern. From this linear model, it can be seen that the zodiacal light has been observed since the sun's position at -60 degrees below the horizon. Recognizing the presence of the zodiacal light is very important to know the time of the appearance of true dawn which is the beginning of the time for the dawn prayer.